The effect of dexmedetomidine vs. atracurium on intubation condition in children - a randomized clinical trial - Mohammad Alipour; Samira Ghanei; Shahrzad Sheikh; Masoud Ghanei; Ahmad Nemati; Shabnam Niroumand (BMC Research Notes)
Abstract Background Using neuromuscular blocking agents (NMBA) in pediatric induction protocol is a challenging matter. Therefore, in this study, we aimed to find a safer way for anesthesia in children. We compared the effects of dexmedetomidine with atracurium on intubation conditions in children aged 6–12 years under general anesthesia. If dexmedetomidine has the similar effect as atracurium, we can use it for intubation and anesthesia of children in situations where the use of atracurium is challenging for any reason. Methods This clinical trial was carried out on children between 6 and 12 years in Mashhad University of Medical Sciences, Mashhad, Iran between January 2018 and February 2020. Participants candidates for tracheal intubation and general anesthesia were enrolled. Patients were distributed into two groups: Patients received Dexmedetomidine (Group D) and patients received Atracurium (Group A). Results We enrolled 25 patients in each group. Most of them were male. The intubation quality score consists of 5 items including laryngoscopy, vocal cord, coughing, jaw relaxation and limb movement was assessed between two groups. This score had no statistically significant difference between study groups. Immediately after induction and one minute after it, heart rate was statistically significant higher in group A than group D (P < 0.001 & P = 0.04 respectively). All of the intubations in our study were successful. More coughing was seen in group A compared with group D (P = 0.01). Conclusion In children aged 6–12 years, the administration of intravenous dexmedetomidine 1mcg/kg over a period of 10 min before the induction of anesthesia with sufentanil 0.3 µg/kg and propofol 3 mg/kg showed no statistically significant difference in quality of intubation score when compared to the use of 0.5 mg/kg atracurium to facilitate intubation. Decreased heart rate and less coughing were observed when using dexmedetomidine. This trial was registered retrospectively in the Iranian Clinical Trials Registry at 2021-24-05 ( https://www.irct.ir/ ), and its registration number is IRCT20201028049177N1.